Honeybee Cultivation Training Apis Mellifera with Forest Farmers Group (KTH) Wana Lestari, Rejo Sari Village, Megang Sakti District, Musi Rawas Regency - Delfy Lensari; Dasir; Lulu Yuningsih; Suyatno; Heripan; Jun Harbi (Altifani Journal: International Journal of Community Engagement, 2024)
Honey bees are social insects that live in colonies. A bee colony consists of around 10,000 to 60,000 bees. The colony consists of a queen (fertile female), hundreds of drones and thousands of worker bees (sterile females). Honey bee cultivation is currently not only oriented towards the economy but also on the aspect of maintaining sustainable forests. The Wana Lestari Forest Farmer Group (KTH) in Rejo Sari Village, Megang Sakti District, Musi Rawas Regency, South Sumatra Province, which is supervised by the Lakitan Bukit Cogong Forest Management Unit (KPH), is developing Apis mellifera bee cultivation. The Community Partnership Program activity partners were carried out at the Lakitan Bukit Cogong KPH Office and at the Wana Lestari Forest Farmer Group (KTH) location in Rejo Sari Village, Megang Sakti District, Musi Rawas Regency, South Sumatra Province on May 27, 2024 - May 31, 2024. The activities carried out were honey bee cultivation training with the initial step of preparing materials for beekeeping and training in the bee breeding process. From the results of this training activity, it can be concluded that the honey bee cultivation training activity at KTH Wana Lestari can be beneficial for KTH members so that it can increase the income of farmer groups.